Sialolithiasis Disease: Clinical Observations of Large Salivary Stones of The Submandibular Salivary Gland - Zhumaev Laziz Razhabovich (Zien Journals, 2023)
This article presents clinical observations related to large salivary stones that occur in the submandibular salivary gland in salivary stone disease. The author describes several clinical cases in which salivary concretions of unusually large sizes were discovered and studied. The article presents data on the localization of stones, sizes, as well as complications resulting from their presence. The analysis of the presented clinical observations allows us to draw conclusions about the unusual and rare nature of this type of salivary stone disease. A detailed description of clinical cases, including the results of multispiral tomography and orthopantomogram, allows us to better understand the features of the formation and development of large salivary stones in the submandibular salivary gland. This article has practical value for dentists and medical specialists involved in the diagnosis and treatment of salivary stone disease. It provides additional knowledge about possible complications associated with large salivary stones, and also emphasizes the importance of timely detection and removal of such stones to prevent possible complications and improve the quality of life of patients.
Keywords: quality; detection; possible; specialists